Do both the research community and the general public share an interest in the sleep–pain relationship, and do they influence each other? - Arnison, Tor; Zhao, Xiang (Frontiers in Psychology, 2023)
Introduction Chronic pain and sleep disturbance bidirectionally influence each other in a negative spiral. Although this academic knowledge is known by researchers, it is imperative to bridge it over to the general public because of its applied implications. However, it is unclear how academia and the general public reciprocally shape each other in terms of knowledge of the sleep–pain relationship. The purpose of this study was (1) to assess the longitudinal trajectories of research on the sleep–pain relationship and the general public’s interest in this topic and (2) to examine whether the academic interest leads to the general public’s interest, or vice versa. Methods We used a Big Data approach to gather data from scientific databases and a public search engine. We then transformed these data into time trends, representing the quantity of published research on, and the general public’s interest in, the sleep–pain relationship. The time trends were visually presented and analyzed via dynamic structural equation modeling. Results The frequency of both published articles and searches soared after 2004. Published research leads to an increased interest in the sleep–pain relationship among the general public but does not predict more published articles. Furthermore, the general public’s interest reinforces itself over time but does not predict published research. Conclusion These results are encouraging because it is essential for research on the sleep–pain relationship to reach a broader audience, beyond the walls of academia. However, to prevent a potential alienation between academic and practical knowledge, we encourage openness among researchers to being inspired by the general public’s knowledge of the sleep–pain relationship.